2019
DOI: 10.35631/ijmtss.210002
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Students’ Attitudes to Choose Agriculture as a Prospective Career: the Moderating Role of Career Prospect

Abstract: This research explores the roles of social status and parental influence on student's attitudes to choose careers in agriculture with the moderating role of career prospects among Malaysian students. The survey method was adopted to collect the data from 183 students who enrolled in agricultural related courses. Data of five major sections such as demographic profiles, attitude, social status, parental influence and career prospect were collected by questionnaire. The PLS-SEM technique was used to analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The results of the (Jalil, 2014) found that academically excellent students, on average, are highly aware of following the flow of technical education at the upper secondary level. Students understand that the field of TVET can produce a skilled workforce, and they know the role of TVET, especially when it comes to skill areas that are very much needed in career prospects (Mat Taib et al, 2019). Parents and the community also need to be highly aware of the importance of the agricultural sector in meeting the needs and demands of the country regarding these needs.…”
Section: Students' Awareness Towards the Selection Of Agricultural Su...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the (Jalil, 2014) found that academically excellent students, on average, are highly aware of following the flow of technical education at the upper secondary level. Students understand that the field of TVET can produce a skilled workforce, and they know the role of TVET, especially when it comes to skill areas that are very much needed in career prospects (Mat Taib et al, 2019). Parents and the community also need to be highly aware of the importance of the agricultural sector in meeting the needs and demands of the country regarding these needs.…”
Section: Students' Awareness Towards the Selection Of Agricultural Su...mentioning
confidence: 99%
“…This academic pathway can potentially lead them to further their studies at the undergraduate and postgraduate levels in public universities and agricultural colleges (Ismail, 2020). Agriculture education may not consistently garner the same popularity or student preference as specific other academic disciplines owing to various factors (Mat Taib et al, 2019;Okoye, 2015). Nevertheless, it is crucial to acknowledge that the level of acceptance and preference for a specific study area can fluctuate depending on geographical location, cultural norms, Vol 12, Issue 3, (2023) E- ISSN: 2226-6348 To Link this Article: http://dx.doi.org/10.6007/IJARPED/v12-i3/19210 DOI:10.6007/IJARPED/v12-i3/19210…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, the African Youth Charter promulgated by the African Union defined youth as people between the ages of 15 and 35 years. In the same vein, the National Youth Development Policy of Nigeria describes youth as consisting of every young person, male or female, between the ages 18 and 35 years (Mat-Taib et al, 2019). The period is often prolonged in developing societies due to the various types of political, social, and economic uncertainties among many other reasons (Joseph et al, 2021).…”
Section: Introductionmentioning
confidence: 99%